A Novel Angiographic Risk Score for Femoropopliteal Interventions. (December 2020) - Iida, Osamu; Takahara, Mitsuyoshi; Soga, Yoshimitsu; Fujihara, Masahiko; Kawasaki, Daizo; Hirano, Keisuke; Choi, Donghoon; Mano, Toshiaki
Purpose: To present a novel angiographic scoring system that stratifies the risk of restenosis after endovascular therapy (EVT) to inform the decision to use paclitaxel-eluting devices in the femoropopliteal segment. Materials and Methods: A prospective, multicenter registry including 1799 limbs of 1578 patients (mean age 74±9 years; 1090 men) with symptomatic peripheral artery disease undergoing intravascular ultrasound–supported femoropopliteal EVT was used as the basis for developing the angiographic score. Multivariable analysis identified baseline patient and limb characteristics associated with restenosis at 12 months. These risk factors for 12-month restenosis were explored using a generalized linear mixed model with a logit-link function in which the inter-institutional and inter-subject variability were treated as random effects. The multiple imputation method was adopted to address missing data. Results of the regression analysis are presented as the odds ratio (OR) with 95% confidence interval (CI). Results: Twelve-month primary patency was estimated to be 65.1% (95% CI 62.7% to 67.5%). After multivariable analysis, distal reference vessel diameter per 1 mm (OR 0.71, 95% CI 0.62 to 0.81, p<0.001), lesion length per 10 cm (OR 1.39, 95% CI 1.19 to 1.62, p<0.001), and chronic total occlusion (OR 1.56, 95% CI 1.15 to 2.10, p=0.004) were independently associated with the 12-month restenosis risk, whereas baseline patient risk factors were not. Compared to bare nitinol stent implantation, plain angioplasty (OR 2.31, 95% CI 1.67 to 3.18, p<0.001) was independently associated with a higher risk of 12-month restenosis, while drug-eluting stents (OR 0.65, 95% CI 0.43 to 0.99, p=0.045) and stent-grafts (OR 0.24, 95% CI 0.12 to 0.50, p<0.001) were independently associated with a lower risk of 12-month restenosis. The angiographic score, which was developed by using the 3 angiographic factors but not the TransAtlantic Society Consensus II (TASC) class, was significantly and independently associated with 12-month restenosis. Conclusion: The current study demonstrated a novel angiographic score for 12-month restenosis after femoropopliteal EVT in a real-world clinical practice. The developed score was significantly and independently associated with the 12-month restenosis risk, but the TASC class was not.